BTN3A is a prognosis marker and a promising target for Vγ9Vδ2 T cells based-immunotherapy in pancreatic ductal adenocarcinoma (PDAC). (2nd January 2018) - Benyamine, Audrey; Loncle, Céline; Foucher, Etienne; Blazquez, Juan-Luis; Castanier, Céline; Chrétien, Anne-Sophie; Modesti, Mauro; Secq, Véronique; Chouaib, Salem; Gironella, Meritxell; Vila-Navarro, Elena; Montalto, Giuseppe; et al.
ABSTRACT: Vγ9Vδ2 T cells are anti-tumor immune effectors of growing interest in cancer including Pancreatic Ductal Adenocarcinoma (PDAC), an especially aggressive cancer characterized by a hypoxic and nutrient-starved immunosuppressive microenvironment. Since Butyrophilin 3 A (BTN3A) isoforms are critical activating molecules of Vγ9Vδ2 T cells, we set out to study BTN3A expression under both basal and stress conditions in PDAC primary tumors, and in novel patient-derived xenograft and PDAC-derived cell lines. BTN3A2 was shown to be the most abundant isoform in PDAC and was stress-regulated. Vγ9Vδ2 T cells cytolytic functions against PDAC required BTN3A and this activity was strongly enhanced by the agonist anti-BTN3A 20.1 mAb even under conditions of hypoxia. In PDAC primary tumors, we established that BTN3A expression and high plasma levels of soluble BTN3A were strongly associated with a decreased survival. These findings may have important implications in the design of new immunotherapeutic strategies that target BTN3A for treating PDAC.